If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21x = -8 + 5x Solving 21x = -8 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 21x + -5x = -8 + 5x + -5x Combine like terms: 21x + -5x = 16x 16x = -8 + 5x + -5x Combine like terms: 5x + -5x = 0 16x = -8 + 0 16x = -8 Divide each side by '16'. x = -0.5 Simplifying x = -0.5
| (x+8)(x+8)=24 | | (-t^2)+8t+21=0 | | 9x-(3x-10)=12-4(6-x) | | (x-4)2-(6-x)2=1 | | -2n+1=-4-1n | | 2n+1=-4-1n | | 21=-8+5x | | x+0.14x=100 | | 2x+6(2x+3)=-10 | | 3L+13=100 | | (x+4)(x+2)=2x | | 2L+13+L=100 | | 5+8x=2x+20 | | x+0.04x=100 | | 5(3x-2)-6x=3(1+3x)-1 | | 75-5x=3x+3 | | v-8.1= | | 3x-10=2x+1 | | M^2-4m+4=4 | | 4x-6=2(x+6) | | 47-3x=5+11x | | 3x+1=6x-8 | | (9+2x)*3=(4x)+11 | | 2x(-x+6)+3(x-1)=0 | | 10x-15=4x+27 | | 5w^2+17w-12=0 | | 5(3x-9)=15(x-3) | | 30-4x=-3x-10 | | Y^2-6y-9=6 | | 1+2x=4-3x | | (3x+10)(x-3)=2x+14 | | (4x^3-4x^2+8x)-(7x^2+3x+6)= |